(untitled) (Journal of Pathology of Nepal, 2017)
Background: Cervical cancer is one of the commonest malignancies and a leading cause of morbidity and mortality among women. The aim of this study was to evaluate the diagnostic value of Papanicolaou (PAP) smear and visual inspection with acetic acid as methods of cervical cancer screening. Materials and Methods: This was a observational cross-sectional study conducted from the period of 2068.11.01 to 2069.11.01. The study population consisted of women with histologically confirmed cervical intraepithelial neoplasia or invasive carcinoma who had undergone prior PAP smear. Results: During the study period 160 patients underwent both PAP smear and cervical biopsy. Of these patients, 49 had a histological diagnosis of cervical intraepithelial neoplasia or invasive carcinoma. The histopathological and cytological diagnoses were compared. Visual inspection with acetic acid status was available for 31 of the 49 cases. The sensitivity of PAP smear was 61%, specificity 97%, positive predictive value 91%, negative predictive value 85% and diagnostic accuracy 86% for detection of cervical neoplasia. Visual inspection with acetic acid had a sensitivity of 74%, specificity 48%, Positive predictive value 64%, Negative predictive value 60% and diagnostic accuracy of 63%. Combining the two procedures increased sensitivity by 26%, Negative predictive value by 11% and diagnostic accuracy by 2 per cent. Conclusion: PAP smear has a higher specificity, Positive predictive value, Negative predictive value and diagnostic accuracy but lower sensitivity than visual inspection with acetic acid. Visual inspection with acetic acid by itself is not an effective screening method. A combination of PAP smear and visual inspection with acetic acidcan ensure adequate screening of cervical neoplasia.